Nearest-Neighbor Projected Distance Regression for Epistasis Detection in GWAS With Population Structure Correction - Arabnejad, Marziyeh; Montgomery, Courtney G.; Gaffney, Patrick M.; McKinney, Brett A. (Frontiers in Genetics, 2020)
Nearest-neighbor Projected-Distance Regression (NPDR) is a feature selection technique that uses nearest-neighbors in high dimension to detect complex multivariate effects including epistasis. NPDR uses a regression formalism that allows statistical significance testing and efficient control for multiple testing. In addition, the regression formalism provides a mechanism for NPDR to adjust for population structure, which we apply to a GWAS of Systemic Lupus Erythematosus (SLE). We also test NPDR on benchmark simulated genetic variant data with epistatic effects, main effects, imbalanced data for case-control design and continuous outcomes. NPDR identifies potential epistatic and other effects that influence the complex SLE disorder.